Representações sociais de professores e estudantes sobre práticas inovadoras no curso de licenciatura em Ciências Biológicas da UEFS - Rosário, Juliana Santos do (2023)
This dissertation presents the results of an investigation carried out in the Graduate Program in Education at the State University of Feira de Santana, Bahia, whose theme is pedagogical innovation in a teacher training course, which bears the title: “Social Representations of professors and students on innovative practices in the Bachelor's Degree in Biological Sciences at UEFS”. The investigation sought to solve the following research problem: what innovations are highlighted in the pedagogical practices of the professors of the Degree in Biological Sciences at UEFS? The general objective of this study was to understand, through the representations of professors and students, which innovation characteristics stand out in the pedagogical practice of the professors of the Bachelor's Degree in Biological Sciences at UEFS. The theoretical basis had as main contribution the following authors: Abric (1997, 1998, 2000, 2003); Behrens (2007); Cunha (2006, 2008, 2009, 20016); Gatti (2006, 2010, 2021); Jodelet (2001, 2003, 2005, 2011); Lucarelli (2009); Moscovici (1978, 2005, 2012); Postic (1984); Ribeiro (2014); Santos (2002, 2010, 2013); Veiga (2002, 2019). To reach the objective outlined, the research adopted a qualitative approach. For data production, the Free Word Association Technique (TALP) was applied to 72 (seventy-two) students and semi- structured interviews with stimulus questions with 4 (four) professors and 4 (four) students of the Degree in Sciences Biologicals from UEFS. Data analysis was inspired by Bardin, Content Analysis (2010) and the Theory of the Central Nucleus of Social Representations. In order to test and confirm the central core of the representation, obtained through the TALP, we performed the centrality test. We conclude that the Central Core of the students' innovation SR is Technology, Novelty, Didactics, Methodology and Creativity, although the centrality test does not confirm technology as innovation. The interviews make us infer that, despite knowing the aspects of innovation in higher education, innovation is still shy in the teaching practice of the professors of the studied course, considering that little was found in the interpersonal relationship, as well as in some strategies of teaching, leaving gaps with regard to learning assessment, teaching with research and extension. The results contribute to the growth of knowledge about the importance of innovation in pedagogical action in teacher training courses, in addition, they will be able to contribute to the reflection of university professors and undergraduate students about the importance of innovation in teaching. In short, the research can also contribute so that the training not only of teachers, but also of students in the basic education network is developed in an innovative perspective.